(untitled) (BIMRAD Journal, 2025)
Bangladesh, with its significant coastline, aims to become a developed nation with a robust maritime sector. However, our research finds that current maritime education faces challenges such as outdated curricula, inadequate infrastructure, and limited international collaboration. This research investigates how to transform maritime education by integrating blue economy principles, incorporating modern technologies like AI and IoT, and fostering strong industry-academia partnerships. It aims to create a skilled workforce, develop high-quality programs, achieve international recognition for Bangladeshi institutions, and provide policy recommendations to stakeholders. The findings of this research provides a comprehensive roadmap for policymakers, academicians, and industry stakeholders to implement necessary reforms. This roadmap includes measures such as curriculum reform to align with industry demands, investment in modern training facilities, establishing international collaborations, fostering industry-academia partnerships, and advocating for government policies that support the development of a strong maritime sector. By addressing these challenges and implementing these roadmaps, Bangladesh can develop a world-class maritime education system that contributes to economic growth, sustainable development, and global competitiveness within the maritime sector. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-1-19